Higher Education and Scientific Research Sector in Algeria: What Kind of Challenges and Changes That Are Required for A Better System? - Samah, Souleh (European Scientific Journal, ESJ, 2017)
This paper highlighted the main reforms of the Higher Education and Scientific Research sector in Algeria from the independence (1962) until now (2016), as well as the reality of its scientific production (graduated students’ quality, publication, universities ranking, patents, and research) in the knowledge based economy. This sector needs some serious changes to function better that is what the paper has suggested.